2002
DOI: 10.1046/j.1529-8817.2002.01056.x
|View full text |Cite
|
Sign up to set email alerts
|

RELATIONSHIPS BETWEEN LITTORAL DIATOMS AND THEIR CHEMICAL ENVIRONMENT IN NORTHEASTERN GERMAN LAKES AND RIVERS1

Abstract: We explored statistical relationships between the composition of littoral diatom assemblages and 21 chemical and physical environmental variables in 69 lakes and 15 river sites in the lowland of northeastern Germany. Canonical correspondence analysis with single treatment and with forward selection of environmental variables was used to detect 11 important ecological variables (dissolved inorganic carbon [DIC], Na+, total phosphorus [TP], dissolved organic carbon [DOC], total nitrogen [TN], pH, oxygen saturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
69
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 60 publications
6
69
1
Order By: Relevance
“…Major nutrients [i.e., nitrogen (N) and phosphorus (P)] concentration of surface waters was a primary factor contributing to variation in benthic-algal assemblages (Leland and Porter 2000). These results were similar to the studies of Christie and Smol (1993) and Schönfelder et al (2002), and they also demonstrated that TN and TP were two of the important ecological variables that explained significant (P \ 0.05) directions of variance in the distribution of benthic-algal taxa. TDS was another significant variable affecting the spatial pattern of benthic algae, which was negatively correlated with the third CCA axis (r = -0.509, P = 0.002).…”
Section: Comparison Among Different Groupssupporting
confidence: 77%
“…Major nutrients [i.e., nitrogen (N) and phosphorus (P)] concentration of surface waters was a primary factor contributing to variation in benthic-algal assemblages (Leland and Porter 2000). These results were similar to the studies of Christie and Smol (1993) and Schönfelder et al (2002), and they also demonstrated that TN and TP were two of the important ecological variables that explained significant (P \ 0.05) directions of variance in the distribution of benthic-algal taxa. TDS was another significant variable affecting the spatial pattern of benthic algae, which was negatively correlated with the third CCA axis (r = -0.509, P = 0.002).…”
Section: Comparison Among Different Groupssupporting
confidence: 77%
“…This suggests that on short time scales the response of diatom communities to seasonal temperature variations may be more prominent than the forcing by mean annual temperatures. Other studies focused on the annual succession of diatoms in dimictic lowland lakes (Raubitschek et al, 1999;Schönfelder et al, 2002;Köster & Pienitz, 2006). These studies demonstrate that the seasonal succession of diatoms differs among lakes depending on factors, such as stratification, temperature, nutrients, pH, oxygen saturation, dissolved iron and calcium, maximum water depth, and dissolved organic carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Scheffler and Schönfelder (2004) reported the microflora of Lake Stechlin and their list contains the species number of benthic diatoms. Schönfelder et al (2002) estimated the relationship between littoral diatom composition and environmental factors in northeastern German lakes including Lake Stechlin. In addition, Stechlin is included in the Water Framework Directive monitoring program of Brandenburg and related reports define reference conditions by means of analysis of diatoms (Schönfelder, 2002;Schönfelder et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Schönfelder et al (2002) estimated the relationship between littoral diatom composition and environmental factors in northeastern German lakes including Lake Stechlin. In addition, Stechlin is included in the Water Framework Directive monitoring program of Brandenburg and related reports define reference conditions by means of analysis of diatoms (Schönfelder, 2002;Schönfelder et al, 2005). However, international publications concerning diversity and spatial and temporal distribution of benthic diatoms are lacking.…”
Section: Introductionmentioning
confidence: 99%